Characterization of a Novel Polymeric Bioflocculant Produced from Bacterial Utilization of n-Hexadecane and Its Application in Removal of Heavy Metals - Pathak, Mihirjyoti; Sarma, Hridip K.; Bhattacharyya, Krishna G.; Subudhi, Sanjukta; Bisht, Varsha; Lal, Banwari; Devi, Arundhuti (Frontiers in Microbiology, 2017)
Abstract A novel polymeric bioflocculant was produced by a bacterium utilizing degradation of n-hexadecane as the energy source. The bioflocculant was produced with a bioflocculating activity of 87.8 %. The hydrocarbon degradation was confirmed by GC/MS analysis and was further supported with contact angle measurements for the changes in hydrophobic nature of the culture medium. A specific aerobic degradation pathway followed by the bacterium during the bioflocculant production and hydrocarbon utilization process has been proposed. FT-IR, SEM-EDX, LC/MS and 1H NMR measurements indicated the presence of carbohydrates and proteins as the major components of the bioflocculant. The bioflocculant was characterized for its carbohydrate monomer constituents and its practical applicability was established for removing the heavy metals (Ni2+, Zn2+, Cd2+, Cu2+ and Pb2+) from aqueous solutions at concentrations of 1 – 50 mg L-1. The highest activity of the bioflocculant was observed with Ni2+ with 79.29 ± 0.12 % bioflocculation efficiency.